2014
DOI: 10.6018/analesps.30.3.154231
|View full text |Cite
|
Sign up to set email alerts
|

Application of a child abuse prevention programme in an educational context. [Aplicación de un programa de prevención del maltrato infantil en el contexto educativo]

Abstract: Título: Aplicación de un programa de prevención del maltrato infantil en el contexto educativo. Resumen: El estudio analiza la eficacia de un programa de prevención del maltrato infantil en el contexto educativo. La propuesta de actuación parte de la utilización del cuento como instrumento para la prevención primaria. El programa trata de mejorar las capacidades de los niños para enfrentarse a situaciones potencialmente amenazantes. El programa fue aplicado en 10 colegios de Educación Primaria de Extremadura (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 74 publications
0
0
0
Order By: Relevance
“…However, exposure was relatively low and low correlations were found. Moreno-Manso et al (2014) found that children increased their knowledge of abuse and safety skills and that much of the results were maintained at the 6-month follow-up. They then concluded that stories proved to be an effective method of instruction and that schools must be involved in primary prevention.…”
Section: Discussionmentioning
confidence: 90%
“…However, exposure was relatively low and low correlations were found. Moreno-Manso et al (2014) found that children increased their knowledge of abuse and safety skills and that much of the results were maintained at the 6-month follow-up. They then concluded that stories proved to be an effective method of instruction and that schools must be involved in primary prevention.…”
Section: Discussionmentioning
confidence: 90%